Tackling autonomous driving challenges – how the design of autonomous vehicles is mirroring universal design - Costa, Susana Raquel Pinto (2019)
In the future, the world will be characterized by highly densely populations, with growing share of mobility-impaired/disabled persons, a critical problem regarding the sustainability of the metropolises, whose resolution may reside in autonomous vehicles. A broader range of users will be allowed a, so far, denied mobility in level 4 and level 5 SAE autonomous vehicles, a goal to be accomplished through Universal Design, a design which intends to be the closest possible to the ideal design. For such purpose, Human Factors and Ergonomics are key. Literature review and research have shown that there is evidence of application of the seven Universal Design principles in these new autonomous vehicles and that, given the nature and purpose of the Universal Design, with the increase of autonomy, there is natural increased evidence of Universal Design. A novel model for interaction of the Universal Design influencers is proposed.